2019
DOI: 10.1080/00313831.2019.1650823
|View full text |Cite
|
Sign up to set email alerts
|

Don’t Fear Poetry! Secondary Teachers’ Key Strategies for Engaging Pupils With Poetic Texts

Abstract: Poetry is a key element of many literature curricula but poetry teaching is something with which many teachers struggle. Research indicates that teachers lack experience of poetry as well as subject knowledge and that current high-stakes testing poses challenges. While previous research has investigated teachers' experiences through large quantitative studies, this study focuses on what teachers who are keen readers of poetry regard as key elements of pedagogy. The material comprises 15 interviews with seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 23 publications
1
16
0
10
Order By: Relevance
“…The findings align with those of Ogunnaike and Akinbode (2011) who found that fifty percent of the teachers found teaching poetry boring, while 75 percent found it difficult to comprehend. It further corroborates Sigvardsson (2019), Creely (2018), Daniel, 2013a, Daniel, 2013b, Khatib (2011) and, Akporobaro (2008) who also found that teachers of literature had a strong aversion to teaching poetry.…”
Section: Discussion Of Findingssupporting
confidence: 72%
See 1 more Smart Citation
“…The findings align with those of Ogunnaike and Akinbode (2011) who found that fifty percent of the teachers found teaching poetry boring, while 75 percent found it difficult to comprehend. It further corroborates Sigvardsson (2019), Creely (2018), Daniel, 2013a, Daniel, 2013b, Khatib (2011) and, Akporobaro (2008) who also found that teachers of literature had a strong aversion to teaching poetry.…”
Section: Discussion Of Findingssupporting
confidence: 72%
“…Similarly, Creely (2018) cited earlier research that showed that many teachers are reluctant to teach poetry. Also, Sigvardsson (2019, p.1) acknowledges, “…poetry teaching is something with which many teachers struggle”.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars (e.g. Creely, 2019; Hennessy et al, 2011; Sigvardsson, 2020) regard such aspects as necessities to reinvigorate poetry education. Still, we see the need for further research on this matter, building a sound body of knowledge in order to further teaching approaches, teacher education and the research field.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored students' and teachers' conceptions of poetry and poetry education (e.g. Dahlbäck et al, 2018; Kelly, 2005; Sigvardsson, 2020), and many scholars have argued that poetry is a pedagogical necessity in regard to its intrinsic value as an art form and its cross‐curricular potential (Hennessy et al, 2011; Kleppe and Sorby, 2018; Lambirth et al, 2012; Locke, 2010). In some poetry classrooms, poetry is alive and thriving (Dymoke, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Because of this free association-like self emotional disclosure aspect, poetry has been a significant element of many literature curricula around the world. Especially in secondary school, poetry is written and read to help students understand themselves and their surroundings through development of their interpretations and individual voices (Sigvardsson, 2019). Collie and Slater (1987) emphasize how poetry can teach students the essence of humanity; "... they often explore themes of universal concern and embody life experiences, observations and the feelings evoked by them" (226).…”
Section: The Benefits Of Poetry Education In Secondary Schoolmentioning
confidence: 99%